Confinement of unliganded EGFR by tetraspanin nanodomains gates EGFR ligand binding and signaling - Sugiyama, Michael G.; Brown, Aidan I.; Vega-Lugo, Jesus; Borges, Jazlyn P.; Scott, Andrew M.; Jaqaman, Khuloud; Fairn, Gregory D.; Antonescu, Costin N. (Nature communications, 2023)
The epidermal growth factor receptor (EGFR) is a central regulator of cell physiology. EGFR is activated by ligand binding, triggering receptor dimerization, activation of kinase activity, and intracellular signaling. EGFR is transiently confined within various plasma membrane nanodomains, yet how this may contribute to regulation of EGFR ligand binding is poorly understood. To resolve how EGFR nanoscale compartmentalization gates ligand binding, we developed single-particle tracking methods to track the mobility of ligand-bound and total EGFR, in combination with modeling of EGFR ligand binding. In comparison to unliganded EGFR, ligand-bound EGFR is more confined and distinctly regulated by clathrin and tetraspanin nanodomains. Ligand binding to unliganded EGFR occurs preferentially in tetraspanin nanodomains, and disruption of tetraspanin nanodomains impairs EGFR ligand binding and alters the conformation of the receptor’s ectodomain. We thus reveal a mechanism by which EGFR confinement within tetraspanin nanodomains regulates receptor signaling at the level of ligand binding. EGFR is a receptor that is upregulated in many cancers, but the mechanisms that control EGFR function are incompletely understood. Here the authors used single particle tracking to identify a role for tetraspanin CD81 in EGFR ligand binding, mobility, and signaling.